Draft Annual Plan 1971-72 Government of Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1971)
Since liberation 1961 the Territory of Goa, Daman and Din has been experiencing stresses and strains and strains and strains normal in the transitional stage. The problem faced immediately after the liberation was the integration of the Region with the rest of the country economically. The Territory comprises of 3 land blocks separated from each other by a distance of over 300 miles. The Territory covers an area of 3706 sqm. of (974%) is in Goa, Daman and Diu account for 57 and 38 sqm Respectively. The population of the Territory was 626667 in 1961 Census and was estimated at 6435OO in 1966. This population lives in 13 towns and 247 villages. "
Planning Department Secretariat Panaji Goa
Planning Department Secretariat Panaji Goa
Keywords: Introduction and overall strategy of Development during the Fourth Five Year Plan; Socio-Economic situation and the Physical Achievements; Financial outlook; Sectoral Programmes and Allocations; Outlay and Expenditure Programme; Agricultural and Allied Sectors; Animal Husbandry Dairy and Milk Supply; Cooperation and Community Development; Industries and Mines